2020
DOI: 10.33902/jpr.2020059790
|View full text |Cite
|
Sign up to set email alerts
|

Investigating special education teachers knowledge and skills: Preparing general teacher preparation for professional development

Abstract: Including students with special needs in the general education classroom requires that teachers adapt their approaches to teaching to meet all students' needs. However, general education teachers are not always fully aware how best to serve special populations. This study examines what skills and knowledge special education educators feel that general education teachers and teacher candidates need in order to work with students with special needs in the inclusive environment. The researchers interviewed twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…These findings are not surprising as there are several studies in the current literature indicating that general education teachers do not feel prepared to work with students with special educational needs in their classrooms (Byrd & Alexander, 2020;Page & Davis, 2016;Sime-Cummins, 2015). As previous research has shown, it is important for general education teachers to possess a specific expertise and pedagogy to meet the diverse needs of these students in the inclusive classroom (Byrd & Alexander, 2020, Dingle et al, 2004. This can be improved through improved teacher co-operation such as collaboration modules between general education and special education teachers (McKenzie, 2015) Some participants (teacher 3, 4) also consider it to be important to work with pupils with special needs in their own resource room, and not in mainstream education.…”
Section: Discussionmentioning
confidence: 76%
“…These findings are not surprising as there are several studies in the current literature indicating that general education teachers do not feel prepared to work with students with special educational needs in their classrooms (Byrd & Alexander, 2020;Page & Davis, 2016;Sime-Cummins, 2015). As previous research has shown, it is important for general education teachers to possess a specific expertise and pedagogy to meet the diverse needs of these students in the inclusive classroom (Byrd & Alexander, 2020, Dingle et al, 2004. This can be improved through improved teacher co-operation such as collaboration modules between general education and special education teachers (McKenzie, 2015) Some participants (teacher 3, 4) also consider it to be important to work with pupils with special needs in their own resource room, and not in mainstream education.…”
Section: Discussionmentioning
confidence: 76%
“…The mathematics teachers easily help the students to solve mathematical problems through a continuum of simple to complex forms. The programs also capitalize on effective instructional methodologies, which harness the skills of learners when they are young and malleable (Byrd & Alexander, 2020;Andenet, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Further, "While pre-service teachers gained some knowledge and developed many positive attitudes towards inclusive education, this was insufficient to instil confidence and capacity to ensure inclusive teaching in the classrooms" (Chhetri, 2019, p.11). This in turn can have negative impact towards teacher's quality of interaction with the students and garner stress to the teacher (Byrd & Alexander, 2020).…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…While students with special education needs are included in the general classroom setting, teachers are required to adapt their teaching approaches to meet all students' needs (Byrd & Alexander, 2020). However, they noted that general teachers are not aware completely as to how to support students with special need.…”
Section: Introductionmentioning
confidence: 99%